A newly synthesized N, O group modified hypercrosslinked resin with effective uptake towards polyphenols from aqueous media: behavior and mechanism. Issue 1 (10th September 2018) - Xu, Chao; Sun, Weizhi; Qin, Xiaoli; Wang, Chuanhong; Yu, Shitao; Xian, Mo; Liu, Huizhou
Abstract: BACKGROUND: A series of hypercrosslinked resins were synthesized by controlling the reaction conditions of the Friedel–Crafts reaction of chloromethylated polystyrene‐co‐divinylbenzene (St‐DVB‐Cl), which realized reasonable adjustment of pore structure, surface area and other physical properties. Based on this, a new N, O modified hypercrosslinked resin (St‐DVB‐NB‐AC2 O) was successfully prepared by the innovative nitration system, and the adsorption behavior of St‐DVB‐NB‐AC2 O was studied under different conditions. The adsorption mechanism between adsorbent and adsorbate was explained by frontier orbital theory and density functional theory. RESULTS: The adsorption capacity of polyphenols on the optimal hypercrosslinked resin (St‐DVB‐NB‐5) was 16.67% higher than that of the optimal commercial resin NDA150. Compared with St‐DVB‐NB‐5, the adsorption increment of hydroxyphenol on St‐DVB‐NB‐AC2 O was 31.42%, which was 1.51–8.36 times higher than commercial materials. The Freundlich model was the most suitable for fitting the equilibrium data. However, the pseudo‐first‐/second‐order rate equation was more appropriate for characterizing the kinetic data, suggesting that the adsorption process might be concerned with a physical reaction. CONCLUSION: The fundamental reason for the large adsorption capacity and fast adsorption rate of St‐DVB‐NB‐AC2 O is its strong physical structure and chemical surface properties, which provided improved guidance for the harmless and resource‐based treatment of phenolic wastewaters. © 2018 Society of Chemical Industry